Money creation and destruction - Salomon Faure; Hans Gersbach (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
We study money creation and destruction in today's monetary architecture and examine the impact of monetary policy and capital regulation in a general equilibrium setting. There are two types of money created and destructed: bank deposits, when banks grant loans to firms or to other banks and central bank money, when the central bank grants loans to private banks. We show that equilibria yield the first-best level of money creation and lending when prices are flexible, regardless of the monetary policy or capital regulation. When prices are rigid, we identify the circumstances in which money creation is excessive or breaks down and the ones in which an adequate combination of monetary policy and capital regulation can restore effciency.
urn:nbn:de:hebis:30:3-420734
Keywords: D50; E4; E5; G21; 330; money creation; bank deposits; capital regulation; zero lower bound; monetary policy; price rigidities